Perbedaan Antara Lamanya Pemberian ASI Eksklusif dengan Inisiasi Menstruasi Post Partum di Puskesmas Kartasura - Pratidiana, Intan Mega; , dr. H Soffin Arfian, Sp.OG; , dr. Endang Widhiyastuti (2016)
Background: The success rate of exclusive breastfeeding in the world and national levels are still low. As already known that exclusive breastfeeding has many benefits for mother and baby. One of the advantages for the mother is for contraception or called Lactation Amenorrhea Method ( LAM ) because breastfeeding can reduce fertility after childbirth. Through breastfeeding, hormone prolactin in the plasma increases affect to GnRH production thus inhibiting ovulation and causing the initiation of menstruation delayed. Purpose: to knowing the difference between the duration of exclusive breastfeeding with the initiation of menstruation post partum in Kartasura Health Center. Method: This study was observational analytic and using cross sectional approach to the 124 respondents who met the inclusion criteria, using purposive sampling technique. Methods of collecting primary data by questionnaire sheets and data analysis with Chi - Square test. Result: obtained p value of 0.001 ( p < 0.05), which is a significant value that means there is a significant difference between exclusive breastfeeding and not exclusive breastfeeding with the initiation of menstruation post partum in Puskesmas Kartasura. Conclusion: There is a significant difference between exclusive breastfeeding and not exclusive breastfeeding with the initiation of menstruation post partum in Kartasura Health Center.